1991
DOI: 10.1182/blood.v78.1.44.44
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant myeloma: laboratory and clinical effects of verapamil as a chemosensitizer

Abstract: Verapamil was evaluated as a chemosensitizer for reversing multidrug resistance in multiple myeloma both in vitro and in clinical trials. Bone marrows from 59 myeloma patients in relapse were evaluated for several resistance parameters: expression of p-glycoprotein (MDR1), doxorubicin (Adriamycin) and vincristine sensitivity, and the ability of added verapamil to reduce resistance to the cytotoxic agents. We found that verapamil was capable of sensitizing myeloma cells that exhibited resistance to doxorubicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(40 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…It has been shown that a number of small, frequently lipophilic cations, as shown by Zamora et al (1988), are able to reverse in vitro the resistance to anthracyclines, Vinca alkaloids, and other natural products (for review, see Ford and Hait, 1990). Indeed, several of these compounds are able to improve the efficacy of anti-cancer drugs in patients with resistant disease (Salmon et al, 1991;Sonneveld et al, 1992). This confirms the clinical relevance of multidrug resistance, already assessed by the finding that MDRl -gene (P-glycoprotein) over-expression frequently occurred in refractory acute leukemias (Marie et al, 1991) and some solid tumors (Goldstein et al, 1989).…”
supporting
confidence: 65%
“…It has been shown that a number of small, frequently lipophilic cations, as shown by Zamora et al (1988), are able to reverse in vitro the resistance to anthracyclines, Vinca alkaloids, and other natural products (for review, see Ford and Hait, 1990). Indeed, several of these compounds are able to improve the efficacy of anti-cancer drugs in patients with resistant disease (Salmon et al, 1991;Sonneveld et al, 1992). This confirms the clinical relevance of multidrug resistance, already assessed by the finding that MDRl -gene (P-glycoprotein) over-expression frequently occurred in refractory acute leukemias (Marie et al, 1991) and some solid tumors (Goldstein et al, 1989).…”
supporting
confidence: 65%
“…Recently, phase I/II clinical trials have evaluated the possibility of circumventing MDR 1 efflux function by adding noncytotoxic agents such as cyclosporin A or verapamil (List et al, 1994;Salmon et al, 1991;Sonneveld et al, 1992). Second-generation reversal agents which lack major immunosuppressive or cardiovascular side-effects are now becoming available.…”
Section: Discussionmentioning
confidence: 99%
“…Pgp is a protein that transports many structurally unrelated substrate drugs. This property has been used to saturate Pgp with non-cytotoxic agents in order to prevent efflux of active drugs, such as verapamil, cyclosporin A and others (Tsuruo et al, 1983;Dalton et al, 1989;Salmon et al, 1991;Solary et al, 1991;Sonneveld et al, 1994). Reversal of MDR by blocking Pgp can be demonstrated in vitro by a functional drug efflux assay and by clonogenic assays.…”
mentioning
confidence: 99%